2022
DOI: 10.1002/jor.25379
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and sex‐specific normative values of bone mineral density in the adult glenoid

Abstract: The objective of this study was to determine the normative bone mineral density (BMD) of cortical and trabecular bone regions in the adult glenoid and its dependence on the subject's age and sex. We analyzed computed tomography (CT) scans of 441 shoulders (310 males, 18–69 years) without any signs of glenohumeral joint pathology. Glenoid BMD was automatically quantified in six volumes of interest (VOIs): cortical bone (CO), subchondral cortical plate (SC), subchondral trabecular bone (ST), and three adjacent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…However, there was no control for the age and sex of the subjects in their study. The decrease of glenoid BMD with age and its dependency on sex for normal subjects has been reported previously [23,24] and we found the same trend in this study (Table A5). However, we could not find any study on the effect of age or BMI on the BMD differences between pathological and CTRL subjects.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, there was no control for the age and sex of the subjects in their study. The decrease of glenoid BMD with age and its dependency on sex for normal subjects has been reported previously [23,24] and we found the same trend in this study (Table A5). However, we could not find any study on the effect of age or BMI on the BMD differences between pathological and CTRL subjects.…”
Section: Discussionsupporting
confidence: 92%
“…The BMD measurement was not considered when a VOI volume was less than 27 (i.e., 3 3 ) mm 3 , and the average trabecular BMD was not considered when all trabecular VOI volumes were below this minimum volume. The BMD measurement method was fully automated and described previously [23,27,39,40]. In addition, in the present study, the VOIs were divided into 8 sectors (octans) of the cylinder defined above and aligned with the posterior-anterior and inferior-superior scapular axes.…”
Section: Glenoid Bmdmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the subgroup analysis showed that the AIP could predict BMD in women below 45 years of age and BMI ≥25 (kg/m 2 ). Several studies have shown that age strongly influences the AIP and BMD ( 52 , 53 ). Our results were inconsistent with those of previous studies that found a negative association between the AIP and BMD in postmenopausal women ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%